About "Love, cheka and death" or the hope of spring - Burguera Nadal, María Luisa (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
We will start first in the study of theoretical assumptions on which we rely to address the analysis: our concept of fictionality and the principles of ideosemantics; we will then stop at the setting of the text, the novel Love, Cheka and Death; we will summarize its argument and briefly inform about the authorship, and then we shall be dealing with the literary genre of the diary, the way in which the text is presented. Once all this has been established, we propose, from the perspective of ideosemantics, some conclusions.
Keywords: Ideosemantics; Love, Cheka and Death; the 20th century Russian novel; diary